Public Employment Effects over the Business Cycle: the Czech Case - Vedunka Kopecna (Charles University in Prague, Institute of Economic Studies (IES), 2016)
The paper contributes to understanding the effects stemming from the public sector employment changes in the Czech Republic and their impacts on the labor market through the lens of a New Keynesian dynamic stochastic general equilibrium model with search and matching frictions. The size of the public sector has been generally expanding over the last decade contrary to many other European countries with the exception of the years 2011 - 2012 when the economic crisis became more evident even in the otherwise financially stable Czech Republic. We model the labor market dynamics across the business cycle and examine the impacts of the varying number of public workers on the labor market variables as private employment, unemployment rate and market tightness as well as on the overall economic growth. We aim at determining whether a portion of unemployment can be explained by either the increased public hiring or shrinking of the number of public employees in the last decade. As the results suggest, in recessionary times the expansion of the public sector managed to keep the unemployment rate from attaining higher values. However, the following turnover of government size development threw the labor market into a deeper crisis than it would have been if the public sector size had remained unaltered.
Keywords: E37; J21; J45; J48; J64; 330; search and matching frictions; DSGE; labor market; public employment